A Networked Self and Birth, Life, Death - Papacharissi, Zizi; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
We are born, live, and die with technologies. This book is about the role technology plays in sustaining narratives of living, dying, and coming to be. Contributing authors examine how technologies connect, disrupt, or help us reorganize ways of parenting and nurturing life. They further consider how technology sustains our ways of thinking and being, hopefully reconciling the distance between who we are and who we aspire to be. Finally, they address the role technology plays in helping us come to terms with death, looking at technologically enhanced memorials, online rituals of mourning, and patterns of grief enabled through technology. Ultimately, this volume is about using technology to reimagine the art of life.
Introduction -- Zizi Papacharissi -- Numerical being and non-being: probing the ethos of quantification in bereavement online -- Amanda Lagerkvist -- Co-Creating Birth and Death on Social Media -- Tama Leaver -- Imagining the future through the lens of the digital: parents narratives of generational change -- Sonia Livingstone and Alicia Blum-Ross -- Storytelling the Self into Citizenship: How Social Media Practices Facilitate Adolescent and Emerging Adult Political Life -- Lynn Schofield Clark and Regina Marchi -- Family life in polymedia -- Mirca Madianou -- Every Click You Make, Ill Be Watching You: Facebook Stalking and Neoliberal Information -- Ilana Gershon -- Formative Events, Networked Spaces, and the Political Socialization of Youth -- Neta Kligler-Vilenchik and Ioana Literat -- Defying Death: Black Joy as Resistance Online -- Catherine Steele and Jessica Lu -- Young People and Digital Grief Etiquette -- Crystal Abidin -- Deconstructing Immortality? Identity Work and the Death of David Bowie in Digital Media -- Johanna Sumiala -- The afterlife of software -- Michael Stevenson and Robert W. Gehl -- From Personal to Personalized Memory: Social Media as Mnemotechnology -- Robert Prey -- and -- Rik Smit -- --Social media rituals: the uses of celebrity death in digital culture -- Jean Burgess, Peta Mitchell and Felix Victor Mnch -- Ghosts in the Machines: How Centuries of Technological Play with Death Has Helped Make Sense of Life -- Whitney Phillips and Ryan M. Milner--
Includes bibliographical references and index.
Also available in print format.
Keywords: augmented or virtual reality; digital media; journalism; live reporting; networked platforms; networks; online spaces; storytelling; Life change events; Internet -- Social aspects; Technology -- Social aspects; Electronic books